The United Nations - Connolly, Sean, 1956- (London : Franklin Watts, 2009)
Describes the history of the United Nations, its peacekeeping missions, and views of those who support or criticize the UN.
A world free of war and problems? -- Setting the scene -- Birth of the UN -- A global reach -- Keeping the peace -- Human rights -- Help on many fronts -- Looking to the future -- Playing your part.
"A+.".
Includes bibliographical references (p. 45) and index.
6.7
5-8
Keywords: United Nations